Pengaruh Harga, Kualitas Produk Dan Kualitas Pelayanan Terhadap Loyalitas Pelanggan Pada Samantha Fashion - Wiwid Prihartono; Rois Arifin; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study aims to determine the effect of price, product quality and service quality on customer loyalty at Samantha Fashion. A sample of 75 respondents from 33 questionnaires distributed to Samantha Fashion customers. The analysis used in this research is multiple linear regression model with SPSS analysis tool. The results showed that simultaneously product quality, service quality, price and location had a significant effect on customer loyalty. While partially product quality, service quality, price and location have a significant effect on customer loyalty. Keywords: Price, Product Quality, Service Quality, Customer Loyalty